Feasibility and acceptability of using the novel urine-based FujiLAM test to detect tuberculosis: A multi-country mixed-methods study. (May 2022) - Chenai Mathabire Rücker, Sekai; Lissouba, Pascale; Akinyi, Milcah; Vicent Lubega, Alex; Stewart, Rosanna; Tamayo Antabak, Natalia; Taremwa Mugisha, Ivan; Ohler, Liesbet; Macuácua, Hélder; Atieno, May; Muyindike, Winnie; Turyahabwe, Stavia; et al.
Highlights: FujiLAM is feasible to implement at point-of-care using existing infrastructure. FujiLAM can be performed in laboratory and consultation or other spaces. FujiLAM adequately performed by any health worker including lay health workers. FujiLAM well accepted by users and managers, perceived as easy to perform. Selection of users should consider expected test demand and existing user workload. Abstract: Background: The novel urine-based FujiLAM test identifies tuberculosis in HIV-positive patients but may be challenging to use at point-of-care (POC). Objectives: We assessed the feasibility and acceptability of using the FujiLAM test at point of care in outpatient settings. Methods: We conducted a mixed methods study in four outpatient settings in Kenya, Mozambique, South Africa, and Uganda between November 2020 and September 2021. The test was performed at POC in existing clinic laboratories and consultation spaces. We performed direct observations in the four health facilities, individual questionnaires, proficiency testing evaluations, and individual interviews among healthcare workers performing the FujiLAM test (healthcare workers), and group discussions with programme managers. Results: Overall, 18/19 (95%) healthcare workers and 14/14 (100%) managers agreed to participate in the study. Most assessed healthcare workers, including lay health workers (10/11; 91%), met the minimum required theoretical knowledge and practical skill in performing the FujiLAM test. Most healthcare workers (17/18; 94%) found the FujiLAM test overall " Easy/Very easy " to perform. Some challenges were mentioned: many timed steps (5/18; 28%); ensuring correct incubation period (5/18; 28%); test result readability (4/18; 22%); and difficulties with cartridge buttons (3/18; 17%). Half of the healthcare workers regularly performing the test (4/7; 57%) found it " Easy " to integrate into routine activities. Most healthcare workers and managers believed that any healthcare worker could perform the test after adequate training. Conclusions: Implementing the FujiLAM test in outpatient POC settings is feasible and acceptable to healthcare workers and managers. This test can be performed in various clinic locations by any healthcare worker. The timed, multi-step test procedure is challenging and may affect the workload in resource-constrained health facilities.